Decision making within missing person incidents - Harrington, Kyle (2019)
Every year the police receive around a quarter of a million reports of missing people in England and Wales alone. Missing Incidents are not only traumatic and potentially dangerous for those involved, but are also likely to contribute to overall public spending; both with respect to the resources required for Missing Person searches, but also due to the increased likelihood of the breakdown of familial care following difficult to manage behaviours. Effective responses to these incidents are imperative, but there is little understanding of how missing person incidents unfold from the perspective of carers and parents. The thesis draws together several disparate research areas, alongside original research, which helps to elucidate how those responsible for a person with care and support needs search, navigate and make decisions under stress and lays a framework of understanding for future research. The work described in this thesis takes a three stage approach; description, prediction and intervention, in order to develop a systematic understanding of how missing incidents unfold, how decision-making within missing incidents can be predicated, and ultimately how technology could be used to address the problem. An initial interview study describes how missing incidents unfold and identifies the important decisions made by carers and search and rescue volunteers. Using this understanding, a vignette study was conducted which led to the development of a predictive model of behaviour during missing person search and the identification of factors which influence decision-making under these conditions. Effective communication is a crucial requirement for carers conducting Missing Person searches; both for material assistance and emotional support. Based on these findings, the final study of this thesis tested a novel prototype technology using an experimental design in a naturally occurring environment. Several evidence-based recommendations were produced as a result of this work which are intended to inform the design of new technologies for supporting missing person searches and may be of use to technology developers, policy-makers, care providers and other stakeholders.